Political scenario and media contributions in the process of devaluation of Science in Brazil (Research, Society and Development, 2020)
This article aims to contribute to the process of reflection on the situation of science today, the role that the media has been playing and the capacity for critical thinking that society must develop. For this, a brief contextualization of the history of science is made. The article was developed by events and news published in 2019 about science in Brazil, with the theoretical contribution of a study that verified the development of science. The bibliographical research cut dealt with the history of science, the Kuhnian and Popperian conception and also the contributions of the media and the internet in the process of manipulation and dissemination of information. The result shows that a conservative political discourse, enhanced by digital and television media, which ignores existing crises and causes apathy among the population for scientific knowledge. It is concluded, therefore, that society must reflect on the contributions of scientific knowledge and combat the messages that harm Brazilian science.